Towards More Understanding of the Financial Leverage Controversy The Evidence of the Industrial Firms at Amman Stock Exchange - Al Momamni, Mohammed Abdullah; Obeidat, Mohammed Ibrahim (International Journal of Economics and Financial Issues, 2017)
The study objects for investigating the most important internal determinants of financial leverage of the listed industrial firms at Amman Stock Exchange (ASE). It is a cross sectional study that it used the issued data of the total listed industrial firms at ASE, where the total number of these firms till the end of 2015 is 48. Seven independent variables the study takes into consideration including firms’ size, liquidity, profitability, assets tangibility, earnings volatility, growth opportunities, and non-debt tax shield. Descriptive statistics, and simple and multiple linear regression methods are used in hypotheses testing. The study shows that liquidity, profitability, tangibility, each of which, have a significant impact on earnings volatility, where other independent variables that the study took into consideration, have no impact. Keywords: Financial Leverage, Capital Structure, Assets tangibility, non-debt tax shield, earnings volatility, and Return on Assets JEL Classifications: G32, M41